Production and evaluation of seaweed-containing plant growth adjuvant formulation - Illera-Vives, Marta (2022)
Seaweed has long been known to be an effective fertilizer improving soil quality and also a biostimulant of plant growth. Seaweed contains all the macro and micronutrients needed for plant growth (Verkleij 1992). Also, it has nitrogen (N) content similar to that of most animal manures, high content in potassium (K) (especially brown seaweed) and a modest amount of phosphorus (P) (Stephenson 1974; Senn and Kingman 1978). Seaweed improves soil quality, mainly as a result of its high content in phycocolloids resulting in increased structure, water retention and exchange capacity (Metting et!al. 1990; Lynn 1972; Khan et!al. 2009). By virtue of its high Calcium (Ca) content and the presence of alginates capable of binding aluminium, seaweeds additionally have liming effects (Crouch et! al. 1990; López- Mosquera and Pazos 1997; Eyras et! al. 1998). Also, it facilitates the growth of bene"cial microbiota, thereby increasing biological activity in soil (Kuwada et!al. 2000, 2006; Chen et!al. 2003; Khan et!al. 2009).